Molecular mechanisms of plastic biodegradation by the fungus Clonostachys rosea - Victor Gambarini; Nikolai Pavlov; Paul Young; Stephanie Dawes; Arnaud Auffret; Joanne M. Kingsbury; Lloyd A. Donaldson; Dawn A. Smith; Louise Weaver; Olga Pantos; Kim M. Handley; Gavin Lear (mBio)
ABSTRACT Microbial degradation can provide an avenue for the remediation of plastic pollution, contributing to the urgent environmental problem of global plastic waste. We demonstrate the degradation of polycaprolactone (PCL) by Clonostachys rosea and elucidate its underlying molecular mechanisms. We constructed the genome of this fungal strain and monitored changes in gene expression when exposed to PCL. Twelve genes linked to PCL degradation were found in the genome of C. rosea, and some of them were upregulated in the presence of the plastic, including genes coding for two cutinases. We heterologously expressed the enzymes coded by both genes and confirmed their activity against PCL polymers. We also demonstrate that one of the enzymes was active against polyethylene terephthalate polymers. Glucose inhibited the expression of both genes, completely halting the plastic biodegradation process, possibly serving as a preferred and readily metabolizable carbon source compared with PCL. We confirm the presence of key metabolic pathways linked to PCL degradation in C. rosea, including fatty acid degradation, providing further evidence of the mechanisms central to plastic biodegradation.IMPORTANCEPlastic pollution is one of our most pressing environmental challenges, with billions of tons of plastic waste accumulating in our ecosystems. While recycling helps, it cannot fully address this crisis, making it crucial to find new solutions. Our study reveals how a common soil fungus, Clonostachys rosea, can break down certain plastics, specifically polycaprolactone and polyethylene terephthalate. We identified the exact genes and enzymes responsible for this ability and showed how different environmental conditions affect the fungus's plastic-degrading capabilities. Notably, we discovered that adding glucose completely stops the fungus from breaking down plastic, suggesting that careful control of growth conditions is essential for effective plastic degradation. These findings are significant because they provide a detailed blueprint for optimizing plastic biodegradation using fungi, potentially leading to more effective ways to tackle plastic pollution. This research represents a crucial step toward developing practical, environmentally friendly solutions for plastic waste management.